THE DIFFICULTIES ENCOUNTERED BY NON-ENGLISH DEPARTMENT STUDENTS IN SPEAKING ENGLISH - Sudjasmara, Deastika Bayuning (2013)
This research, titled "The Difficulties Encountered by Non-English Department Students in Speaking English", is a case study at a college of nursing in Bandung. It is conducted to investigate difficulties encountered by non-English department students (NEDS) in speaking English, which is divided into two aspects: linguistic and psychological aspects. It also aims to find the strategies used to overcome the difficulties. This research employs a case study with qualitative approach, involving 25 students of a college of nursing in Bandung. Questionnaire and interview are employed to gain the data. From the study, it is found that the major difficulties encountered by NEDS are in vocabulary and nervousness. Moreover, to overcome the difficulties encountered, this study find some strategies used by the NEDS in speaking English and the most strategies used by the students are using Bahasa Indonesia, asking for help, being quiet, smiling or laughing and taking risk. Keywords: difficulties, speaking, NEDS, college of nursing Penelitian berjudul "The Difficulties Encountered by Non-English Department Students in Speaking English" ini merupakan sebuah studi kasus di sebuah akademi keperawatan di Bandung. Penelitian ini dilakukan untuk mengetahui kesulitan yang dihadapi oleh mahasiswa non-bahasa Inggris dalam berbicara bahasa Inggris, yang dibagi kedalam dua aspek: aspek kebahasaan dan psikologi. Penelitian ini juga bertujuan untuk mengetahui strategi yang digunakan untuk mengatasi kesulitan tersebut. Penelitian merupakan studi kasus dengan menggunakan pendekatan kualitatif yang melibatkan 25 murid dari salah satu akademi keperawatan di Bandung. Angket dan wawancara dilakukan untuk memperoleh data. Dari penelitian ini ditemukan bahwa kesulitan terbesar yang dialami mahasiswa non-bahasa Inggris dalam berbicara bahasa Inggris adalah perbendaharaan kata dan rasa gugup. Penelitian ini juga menemukan bahwa untuk mengatasi kesulitan berbicara dalam bahasa Inggris, mahasiswa menggunakan beberapa strategi diantaranya menggunakan bahasa Indonesia, bertanya, diam, senyum atau tertawa dan mengambil resiko. Kata kunci: kesulitan, berbicara, mahasiswa non-bahasa Inggris, akademi keperawatan